Strategi Guru dalam Membina Kontrol Perilaku Peserta Didik di MA Al Manar Tanjungtani Prambon Nganjuk - Syamsul Ma’arif; Muhammad Khoirul Amini Hasby; A. Jauhar Fuad (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2024)
Teachers play an important role in the learning process, including guiding and controlling student behavior. This study aims to analyze teacher strategies in fostering behavior control at MA Al-Manar. The research uses a qualitative approach with data collected through interviews, observations, and documentation, supported by relevant literature. Data analysis includes reduction, presentation, and conclusion drawing. The results show that teacher strategies in behavior control are influenced by various factors, especially in determining appropriate forms of guidance. These strategies are closely related to the affective domain, including feelings, motivation, and attitudes. The study concludes that emotional aspects play a significant role in shaping students’ behavior in the learning process.